A companion to the preclinical common data elements for rodent models of pediatric acquired epilepsy: A report of the TASK3-WG1B, Pediatric and Genetic Models Working Group of the ILAE/AES Joint Translational Task Force - Katsarou, Anna-Maria; Kubova, Hana; Auvin, Stéphane; Mantegazza, Massimo; Barker-Haliski, Melissa; Galanopoulou, Aristea S; Reid, Christopher A; Semple, Bridgette D (Epilepsia open, 2022)
Epilepsy syndromes during the early years of life may be attributed to an acquired insult, such as hypoxic-ischemic injury, infection, status epilepticus, or brain trauma. These conditions are frequently modeled in experimental rodents to delineate mechanisms of epileptogenesis and investigate novel therapeutic strategies. However, heterogeneity and subsequent lack of reproducibility of such models across laboratories is an ongoing challenge to maintain scientific rigor and knowledge advancement. To address this, as part of the TASK3-WG1B Working Group of the International League Against Epilepsy/American Epilepsy Society Joint Translational Task Force, we have developed a series of case report forms (CRFs) to describe common data elements for pediatric acquired epilepsy models in rodents. The "Rodent Models of Pediatric Acquired Epilepsy" Core CRF was designed to capture cohort-general information; while two Specific CRFs encompass physical induction models and chemical induction models, respectively. This companion manuscript describes the key elements of these models and why they are important to be considered and reported consistently. Together, these CRFs provide investigators with the tools to systematically record critical information regarding their chosen model of acquired epilepsy during early life, for improved standardization and transparency across laboratories. These outcomes will support the ultimate goal of such research; that is, to understand the childhood onset-specific biology of epileptogenesis after acquired insults, and translate this knowledge into therapeutics to improve pediatric patient outcomes and minimize the lifetime burden of epilepsy.
Keywords: induction; hypoxic ischemic injury; status epilepticus; seizure; infantile spasms; brain injury